2017
DOI: 10.3390/md15030061
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of Antioxidant Peptides from Protein Hydrolysate of Scalloped Hammerhead (Sphyrna lewini) Cartilage

Abstract: The aim of this study was to purify and identify peptides with antioxidant properties from protein hydrolysate of scalloped hammerhead (Sphyrna lewini) cartilage. Cartilaginous proteins of the scalloped hammerhead were extracted by guanidine hydrochloride, and three antioxidant peptides, named enzymolysis peptide of scalloped hammerhead cartilage A (SCPE-A), SCPE-B and SCPE-C, were subsequently isolated from the hydrolysate of the cartilaginous proteins using ultrafiltration and chromatography. The amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…Though, the DH reported for goby Figure 5: Reductive Potential of Mormyrus rume Muscle Protein Hydrolysates muscle protein using crude enzymes from different sources (Nasri et al, 2014) was lower compared to the present result, the shape of hydrolysis curves is similar. The degree of hydrolysis reported in the present work compared well with the DH published by Li et al (2017) for scalloped hammerhead (Sphyrna lewini) cartilage which ranges from 18.33% to 23.72%. In contrast to the above reports, higher DH (76.29% and 63.49%) was published for red tilapia (Oreochromis niloticus) byproduct protein using thermolysin and alcalase for hydrolysis, respectively (Roslan et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Though, the DH reported for goby Figure 5: Reductive Potential of Mormyrus rume Muscle Protein Hydrolysates muscle protein using crude enzymes from different sources (Nasri et al, 2014) was lower compared to the present result, the shape of hydrolysis curves is similar. The degree of hydrolysis reported in the present work compared well with the DH published by Li et al (2017) for scalloped hammerhead (Sphyrna lewini) cartilage which ranges from 18.33% to 23.72%. In contrast to the above reports, higher DH (76.29% and 63.49%) was published for red tilapia (Oreochromis niloticus) byproduct protein using thermolysin and alcalase for hydrolysis, respectively (Roslan et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Low-MW antioxidant peptides have a highly pronounced ability to hold back the oxidative stress because they can easily interact with target radicals to terminate the free radical chain reactions [5,49,50]. In addition, Li et al reported that the antioxidant activities of protein hydrolysates with average MW (AMW) from 0.64 kDa to 257.19 kDa were negatively related to the logarithm of their AMW [31].…”
Section: Structure-activity Relationship Of Mmp-4 Mmp-7 and Mmp-12mentioning
confidence: 99%
“…For in vitro systems where no chemical oxidizing agent is added, but LPO occurs through different pathways, lipid peroxides thus formed become the main oxidizing compounds in the medium, and LPO can be quantified by using a reagent prone to be oxidized by lipid peroxides (amount of reagent lost can be converted in amount of lipid peroxides). This is the case of the thiocyanate method [68], which has been used to track LPO in lipid-solution-based LPIP assays (as described in the next section) [69][70][71][72][73][74][75][76][77][78]. Given the lack of an oxidizing trigger in these assays, the capacity of the medium to oxidize iron (II) to iron (III) is directly proportional to the concentration of lipid peroxides.…”
Section: On the Quantification Of Lipid Peroxidationmentioning
confidence: 99%
“…Importantly, one should note that quantifying the lipid peroxides of a sample is a measure of LPO that will decay along time, as lipid peroxides degrade into smaller molecules; thus, it is a measure of "early lipid peroxidation". In the thiocyanate method, ferrous ions are oxidized into ferric ions, which in turn form a colored complex with thiocyanate (ferric thiocyanate), with maximum absorbance at 485 nm [68][69][70][75][76][77].…”
Section: On the Quantification Of Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation